Recruitment patterns in a large international randomized controlled trial of perioperative care in cancer patients - Aaron Gazendam; Anthony Bozzo; Patricia Schneider; Victoria Giglio; David Wilson; Michelle Ghert (Trials, 2021)
Abstract Introduction The Prophylactic Antibiotic Regimens in Tumor Surgery (PARITY) randomized controlled trial (RCT) was the first study to prospectively enroll and randomize orthopedic oncology patients in multiple centers internationally. The objective of this study was to describe recruitment patterns, to examine the differences in enrollment across different PARITY sites, and to identify variables associated with differing levels of recruitment. Methods Data from this study was obtained from the PARITY trial Methods Center and records of correspondence between the Methods Center and recruiting sites. We performed descriptive statistics to report the recruitment patterns over time. We compared recruitment, time to set up, and time to enroll the first patient between North American and international sites, private and public healthcare models, and the presence or absence of research personnel. Two-tailed non-paired t tests were performed to test average monthly recruitment rates between groups. Results A total of 602 patients from 36 North American and 12 international sites were recruited from 2013 to 2019. North American sites were able to become fully enrollment-ready at an average of 19.5 months and international sites at an average of 27 months. Once enrolling, international sites were able to enroll 0.59 patients per/month whereas North American sites averaged a monthly recruitment rate of 0.2 patients/month once enrolling. Sites with research personnel reached enrollment-ready status at an average of 19.3 months and sites without research support at an average of 30.3 months. Once enrolling, the recruitment rate was 0.28 patients/month and 0.2 patients per month for sites with and without research support, respectively. Publicly funded sites had a monthly enrollment of 0.4 patients/month whereas privately funded sites had a monthly enrollment rate of 0.17 patients/month. Conclusions As a collaborative group, the PARITY investigators increased the pace of recruitment throughout the trial, likely by increasing the number of active sites. The longer time to start-up at international sites may be due to the complex governing regulations of pharmaceutical trials. Nevertheless, international sites should be considered essential as they recruited significantly more patients per month once active. The absence of research support personnel may lead to delays in the time to start-up. The results of the current study will provide guidance for choosing which sites to recruit for participation in future collaborative clinical trials in orthopedic oncology and other surgical specialties. Trial registration ClinicalTrials.gov NCT01479283 . Prospectively registered on November 24, 2011